2012
DOI: 10.1371/journal.pone.0038003
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Inversion: Running Animals and Robots Swing like a Pendulum under Ledges

Abstract: Escaping from predators often demands that animals rapidly negotiate complex environments. The smallest animals attain relatively fast speeds with high frequency leg cycling, wing flapping or body undulations, but absolute speeds are slow compared to larger animals. Instead, small animals benefit from the advantages of enhanced maneuverability in part due to scaling. Here, we report a novel behavior in small, legged runners that may facilitate their escape by disappearance from predators. We video recorded coc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
18
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 37 publications
0
18
0
Order By: Relevance
“…Cockroaches use rigid, jointed exoskeletons to run rapidly at speeds approaching 1.5 m·s −1 (31), climb up walls (11,32), race along ceilings (33), and swing stealthily under ledges out of sight (34). However, materials science has revealed that the stiffness of exoskeletal tissue can differ by eight orders of magnitude (35)(36)(37)(38), permitting the possibility that cockroaches with powerful propulsive appendages might also retain the advantages of soft-bodied animals capable of conforming to their environment (39).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Cockroaches use rigid, jointed exoskeletons to run rapidly at speeds approaching 1.5 m·s −1 (31), climb up walls (11,32), race along ceilings (33), and swing stealthily under ledges out of sight (34). However, materials science has revealed that the stiffness of exoskeletal tissue can differ by eight orders of magnitude (35)(36)(37)(38), permitting the possibility that cockroaches with powerful propulsive appendages might also retain the advantages of soft-bodied animals capable of conforming to their environment (39).…”
mentioning
confidence: 99%
“…We selected the American cockroach, Periplaneta americana, because of its high speed (31), maneuverability (34,40), robustness (41), and tenacity to enter and leave spaces. To determine the smallest horizontal crevice that a cockroach could traverse, we challenged animals with a series of decreasing crevice heights.…”
mentioning
confidence: 99%
“…Given the mites' ability to turn through 180 deg in 6-7 gait cycles, and assuming a stride frequency in the field of 100 Hz, they would be able to accomplish such a turn in less than 0.1 s. The peak angular velocity achieved by a pivoting mite in the current lab trials exceeded 1250 deg s −1 . This pivoting, lateral turn by the mite is comparable in angular velocity to the inversion behavior seen in the cockroach Periplaneta, which uses a similar grappling hook mechanism to pivot vertically around the tarsus of a limb during escape (>1200 deg s −1 ; Mongeau et al, 2012). Unlike Periplaneta, however, the mites continued to cycle their other limbs to move through the turn about the pivoted leg (Fig.…”
Section: Discussionmentioning
confidence: 67%
“…Although the pivoting (or grappling hook) mechanism has been described in inverting cockroaches and geckos (Mongeau et al, 2012), this use of a grappling hook during turning in P. macropalpis differs substantially from that described for most other arthropods. The octopodal gait in the tarantula Grammostola mollicoma uses a gait cycle where the ipsilateral legs are reversed during a sharp turn (Biancardi et al, 2011).…”
Section: Discussionmentioning
confidence: 88%
“…The American cockroach, Periplaneta americana, is a highly dynamic running insect, exhibiting a variety of robust and high speed gaits that we use as a model of study for the design of VelociRoACH. P. americana is capable of running at over 50 body-lengths per second (bl/s) and is capable of hexapedal, quadrupedal, and even bipedal locomotion [9], as well as high-speed climbing and rapid inversion [19].…”
Section: Introductionmentioning
confidence: 99%